ROS and cGMP signaling modulate persistent escape from hypoxia in Caenorhabditis elegans. - Lina Zhao; Lorenz A Fenk; Lars Nilsson; Niko Paresh Amin-Wetzel; Nelson Javier Ramirez-Suarez; Mario de Bono; Changchun Chen (PLoS Biology, 2022)
The ability to detect and respond to acute oxygen (O2) shortages is indispensable to aerobic life. The molecular mechanisms and circuits underlying this capacity are poorly understood. Here, we characterize the behavioral responses of feeding Caenorhabditis elegans to approximately 1% O2. Acute hypoxia triggers a bout of turning maneuvers followed by a persistent switch to rapid forward movement as animals seek to avoid and escape hypoxia. While the behavioral responses to 1% O2 closely resemble those evoked by 21% O2, they have distinct molecular and circuit underpinnings. Disrupting phosphodiesterases (PDEs), specific G proteins, or BBSome function inhibits escape from 1% O2 due to increased cGMP signaling. A primary source of cGMP is GCY-28, the ortholog of the atrial natriuretic peptide (ANP) receptor. cGMP activates the protein kinase G EGL-4 and enhances neuroendocrine secretion to inhibit acute responses to 1% O2. Triggering a rise in cGMP optogenetically in multiple neurons, including AIA interneurons, rapidly and reversibly inhibits escape from 1% O2. Ca2+ imaging reveals that a 7% to 1% O2 stimulus evokes a Ca2+ decrease in several neurons. Defects in mitochondrial complex I (MCI) and mitochondrial complex I (MCIII), which lead to persistently high reactive oxygen species (ROS), abrogate acute hypoxia responses. In particular, repressing the expression of isp-1, which encodes the iron sulfur protein of MCIII, inhibits escape from 1% O2 without affecting responses to 21% O2. Both genetic and pharmacological up-regulation of mitochondrial ROS increase cGMP levels, which contribute to the reduced hypoxia responses. Our results implicate ROS and precise regulation of intracellular cGMP in the modulation of acute responses to hypoxia by C. elegans.